2015
DOI: 10.3390/molecules20045616
|View full text |Cite
|
Sign up to set email alerts
|

New Flavonolignan Glycosides from the Aerial Parts of Zizania latifolia

Abstract: Two new flavonolignan glycosides, tricin-4'-O-(threo-β-guaiacylglyceryl) ether 7''-O-β-d-glucopyranose (4) and tricin-4'-O-(erythro-β-guaiacylglyceryl) ether 7''-O-β-d-glucopyranose (5) were isolated from the roots of Zizania latifolia, together with tricin-7-O-β-d-glucopyranose (1), tricin-4'-O-(threo-β-guaiacylglyceryl) ether 7-O-β-d-glucopyranose (2), and tricin-4'-O-(erythro-β-guaiacylglyceryl) ether 7-O-β-d-glucopyranose (3). Their structures were identified on the basis of spectroscopic techniques, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…As demonstrated in our previous study, tricin and its derivatives, including a new flavonolignan salcolin D, were isolated as the active components exerting the anti-inflammatory and anti-allergic activities in ethanol extracts from the aerial parts of Z. latifolia . Lee et al [ 17 ] reported the presence of new flavonolignan groups along with tricin in this plant. In our previous study, the quantitative analysis of 11 compounds present in the ethanol extract from the aerial parts of Z. latifolia (including tricin and its derivatives) confirmed that tricin is the quantitatively major component in the extract (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…As demonstrated in our previous study, tricin and its derivatives, including a new flavonolignan salcolin D, were isolated as the active components exerting the anti-inflammatory and anti-allergic activities in ethanol extracts from the aerial parts of Z. latifolia . Lee et al [ 17 ] reported the presence of new flavonolignan groups along with tricin in this plant. In our previous study, the quantitative analysis of 11 compounds present in the ethanol extract from the aerial parts of Z. latifolia (including tricin and its derivatives) confirmed that tricin is the quantitatively major component in the extract (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…It has long been studied as an extractable portion of various grasses and cereals (family Poaceae), such as wheat, bamboo, oat, maize and rice (Markley and Bailey, ; Vogel et al ., ; Harborne and Hall, ). The extractable tricin can occur in either free form (Nakano et al ., ) or in various conjugated forms, such as tricin‐glycosides (Duarte‐Almeida et al ., ; Van Hoyweghen et al ., ; Bottcher et al ., ), tricin‐lignans (Bouaziz et al ., ; Wenzig et al ., ) and (tricin‐glycoside)‐lignans (Bottcher et al ., ; Lee et al ., ), as shown in Figure . As we recently reported, not all of the tricin‐lignans may be such (Lan et al ., ); as the ones we extracted for metabolite profiling displayed no optical activity and were obviously the result of a remarkable variety of combinatorial coupling products from not just the monolignols but the monolignol acetate and p ‐coumarate conjugates, we contended that these are incipient tricin‐lignins or tricin‐(oligo)lignols or, more generally, flavonolignins or flavonolignols (Lan et al ., ).…”
Section: Introductionmentioning
confidence: 82%
“…(d) Tricin‐(acyl‐glucoside) (Duarte‐Almeida et al ., ). (e) (Tricin‐glucoside)‐lignan (Lee et al ., ).…”
Section: Introductionunclassified
“…Two guaiacylglyceryl tricin isomers of molecular ion peak [M-H]at m/z 525 that were defined as salcolin A and salcolin B 28 . in addition to their glycosides that displayed molecular ion peak [M-H]at m/z 687, and tentatively identified as tricin 4′-O-(erythro-βguaiacylglyceryl ether) glucoside and its threo isomer 29…”
Section: Phytochemical Profiling Of L Chinensis Leaf Extractmentioning
confidence: 99%